Sebuah KOMPARASI METODE NAIVE BAYES DAN DECISION TREE PADA PREDIKSI LONJAKAN PENUMPANG KAPAL DI PELABUHAN TANJUNG API API: Jurnal Wahyunita, Diana | Universitas Bina Darma - ., Wahyunita; Diana (MULTINETICS, 2024)
Tanjung Api - Api Port is a sea crossing port located in Banyuasin Regency, approximately 68 km from Palembang City, South Sumatra. This port connects South Sumatra Province with Bangka Belitung Province, specifically Tanjung Kalian Port in Bangka.The important role of ships as water transportation is of course an impact on the number of ship passengers which increases on certain days. Therefore, ports must be ready to deal with a buildup of passengers at the port. Based on this, researchers carried out passenger surge analysis using the Naive Bayes and Decision Tree methods using the Rapid Miner application. A comparison of the Naïve Bayes and Decision Tree methods is expected to be able to predict the size of the passenger surge on certain days in order to prepare the ship fleet according to needs. Keywords: Naïve Bayes, Rapid Miner, Passenger Surge, Decision Tree.